2022
DOI: 10.1007/s00167-022-07268-w
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-defensin as a diagnostic tool in revision total knee arthroplasties with unexpected positive intraoperative cultures and unexpected culture negative intraoperative cultures

Abstract: Purpose Unexpected-positive-intraoperative-cultures (UPIC) are common in presumed aseptic revision-total-knee-arthroplasties (rTKA). However, the clinical signiicance is not entirely clear. In contrast, in some presumably septic rTKA, identiication of an underlying pathogen was not possible, so-called unexpected-negative-intraoperative-cultures (UNIC). The purpose of this study was to evaluate the potential use of synovial alpha-defensin (AD) levels in these patients. Methods Synovial AD levels from 143 rTKAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This study highlights some of the potential consequences of liberal prescription of postarthroplasty antibiotics and provides a reminder of why judicious use of antibiotics is appropriate [1]. This study found that advanced diagnostic tests such as alpha defensin could be useful when determining the clinical relevance of intraoperative cultures [9]. A recent meta-analysis synthesized the contemporary body of research pertaining to the occurrence of PICs in revision arthroplasty [8].…”
Section: Read This Nextmentioning
confidence: 99%
See 1 more Smart Citation
“…This study highlights some of the potential consequences of liberal prescription of postarthroplasty antibiotics and provides a reminder of why judicious use of antibiotics is appropriate [1]. This study found that advanced diagnostic tests such as alpha defensin could be useful when determining the clinical relevance of intraoperative cultures [9]. A recent meta-analysis synthesized the contemporary body of research pertaining to the occurrence of PICs in revision arthroplasty [8].…”
Section: Read This Nextmentioning
confidence: 99%
“…This study found that advanced diagnostic tests such as alpha defensin could be useful when determining the clinical relevance of intraoperative cultures [9].…”
Section: Read This Nextmentioning
confidence: 99%